The Mediating Role of Brand Image in the Relationship Between Promotion, Price Perception, and Purchase Intention: Evidence from Emerging Market Bottled Water Consumers - Maria Monika Anjelina Manek Gulo; Yeremias Lake (PT Literati Global Network, 2026)
Purpose: This study examines brand image as a mediating mechanism linking promotional strategies and price perception to purchase intention among bottled water consumers in an emerging market context, addressing the need for process-oriented research in price-sensitive Southeast Asian markets. Method/Approach: Cross-sectional survey data from 160 Le Minerale consumers in Kefamenanu City, Indonesia (July-August 2025) were analyzed using partial least squares structural equation modeling (PLS-SEM) with bias-corrected bootstrapping procedures (5,000 resamples). The study tested both direct effects and indirect effects through brand image mediation. Findings: Promotion (β = 0.522, p < 0.001) and price perception (β = 0.348, p < 0.001) strongly influence brand image, which in turn significantly predicts purchase intention (β = 0.487, p < 0.001). Brand image significantly mediates both promotion-purchase intention (indirect effect = 0.254, 95% CI [0.143, 0.365], accounting for 55% of total effect) and price perception-purchase intention relationships (indirect effect = 0.169, 95% CI [0.077, 0.263], accounting for 44% of total effect). The model explains 47% of variance in purchase intention (R² = 0.47) and demonstrates predictive relevance (Q² = 0.36). Limitations: Cross-sectional design limits causal inference. Future research should employ longitudinal designs, examine boundary conditions (product involvement, competitive intensity), and test generalizability across product categories and cultural contexts in Southeast Asia. Implications: Organizations should develop integrated marketing strategies emphasizing brand-building through promotional activities and competitive pricing rather than relying solely on direct promotional tactics. Marketing managers in FMCG sectors should allocate resources to strengthen brand perception as the primary mechanism influencing purchase behavior. Contribution: This study quantifies brand image as the dominant mediating mechanism in emerging markets, demonstrating that indirect effects through brand perception exceed direct effects of marketing variables. Findings extend social cognitive theory and brand positioning literature to price-sensitive, high-competition Southeast Asian contexts where fundamental psychological mechanisms operate when organizational conditions support brand-building practices.